A Communications Perspective on the Use of Visualisations in a Dutch Court for Minor Felonies - Lisanne van Weelden (Utrecht University School of Law, 2019)
Images such as photographs, drawings, animations and videos are everywhere in modern society and are playing an ever-increasing role in court. This general shift from written and spoken language to ‘visual language’ in society has been of interest to language and communication researchers for years. Within the domain of law, however, a lot of the language and communication literature is traditionally focused on written and spoken language. In the first part of this paper we provide a theoretical background in which we discuss how people understand images, what visual literacy means, how images can have persuasive power and can influence people in terms of their emotions, attitudes and decision-making and we talk about how this can play a role in court. Furthermore, we illustrate some gaps in the literature. In the second part of the paper we show, based on a small-scale ethnographic study and systematic observation, how often visualisations are part of the case file in Dutch hearings, what types of images are talked about and/or shown and by whom they are introduced during the hearing. We conclude by discussing what communication scholars find interesting about these observations and we also suggest a number of research opportunities that may be of interest for interdisciplinary research amongst law and communication scholars.